Association Between Nonselective Beta-Blocker Use and Hepatocellular Carcinoma in Patients With Chronic Hepatitis B Without Cirrhosis and Decompensation - Cheng, He-Yun; Lin, Hsiu C.; Lin, Hsiu L.; Uang, Yow S.; Keller, Joseph J.; Wang, Li H. (Frontiers in Pharmacology, 2022)
Background: Nonselective beta-blockers (NSBBs) can reduce the incidence or mortality of certain types of cancers, and NSBBs exert a protective effect on hepatocellular carcinoma (HCC) in patients with cirrhosis. However, the potential preventive effect of NSBBs has not yet been investigated in patients with chronic hepatitis B (CHB) who have a high HCC risk regardless of the presence of underlying cirrhosis. Aim: This study evaluated the association between NSBB use and HCC incidence in patients with CHB without cirrhosis and decompensation. Methods: From the 2000 Longitudinal Generation Tracking Database, we enrolled patients who were newly diagnosed as having CHB from January 2001 to December 2011 and then followed them up for at least 5 years. To estimate the causal effect of NSBBs on the time-to-event outcomes of HCC, a marginal Cox proportional hazards model was used to calculate hazard ratios (HRs) and 95% confidence intervals (CIs). Results: After adjustment, no significant benefit of HCC risk reduction was observed between the NSBB users and nonusers (adjusted HR, 0.82; 95% CI, 0.52–1.31). The cumulative defined daily dose (cDDD) analysis revealed no significant dose correlation among the three groups [adjusted HR (95% CI): 1.08, (0.56–2.05), 0.54 (0.17–1.77), and 0.76 (0.40–1.42) in the <90 cDDD, 90 to <180 cDDD, and ≥180 cDDD groups, respectively]. Duration-dependent associations were not observed. Multivariable stratified analysis results demonstrated that HCC risk markedly decreased in the patients aged >55 years (adjusted HR, 0.49; 95% CI, 0.25–0.96; p = 0.04). Conclusion: NSBB did not significantly prevent HCC in the patients with CHB infection without cirrhosis and decompensation. This study provided one of valuable results that it is not clinically required to use NSBBs as recommended chemoprevention for HCC in high-risk patients who have CHB.